Penerapan Metode Preference Selection Index (PSI) Dalam Pemilihan Perguruan Tinggi Swasta Program Studi IT di Provinsi Kalimantan Timur - Nursobah Nursobah (STMIK Budi Darma, 2021)
Higher education is a place for students to study after graduating from high school/vocational high school in order to continue their higher education level, at college students study according to the majors they are interested in as a provision to find work after graduating from campus that. In choosing a college, it is necessary to choose a university that has good quality and can be recognized by a diploma from the campus. The Department of Informatics Engineering is one of the majors in the university. The selection of majors also needs to pay attention to the quality of universities and the quality of the existing majors at these universities is considered important because universities are the starting gate to create new knowledge and more knowledge for their students so that students also become someone who is competently trained in the IT field, College selection is mandatory and the number of universities offering the same major often confuses prospective students. Therefore, it is necessary to make the right selection using the Preference Selection Index (PSI) method which is one of the accurate methods in solving decision-making problems. The results showed that alternative A5 had the best value with a final value of 0.67.